Psychological care of patients during the pancreas transplantation process: issues and prospects - Galani, Vasiliki; Villard, Orianne; Olivier, Valérie; Peloso, Andrea; Compagnon, Philippe; Haidar, Fadi; Prada, Paco (Frontiers in Clinical Diabetes and Healthcare, 2023)
Pancreas transplantation for patients with type 1 diabetes is a therapeutic option when other treatments are not effective and physical complications occur. Psychological burden is prominent in patients, and non-adherence to treatment is often one manifestation of such difficulties. Time projection is an important factor affected by chronic disease. The prospect of transplantation has the potential to repair this disruption. It could re-establish a continuity in the patient's self and history, by connecting the future to a life that was only about past and present. Taking care of oneself, adhering to treatment, being part of a long-term therapeutic project and going through transplantation are all processes that need a good ability to self-project in time. This is specifically a domain of psychotherapeutic interventions. In this article, the psychological implications of pancreas transplantation for patients and caregivers alike will be discussed, as well as the role of the psychiatrist in the transplantation process.